Short- and Long-Term Outcomes of Community-Based Art Education among Students in Higher Education - Carolina Blatt-Gross (MDPI AG, 2023)
Advocating for the academic value of community-based art education requires empirical evidence that students are not just participating in community-building activities, but also effectively learning content. Unfortunately, little is known about the short- and long-term cognitive outcomes on student participants, particularly in higher education. Based in a phenomenological methodology with a reflective lifeworld research design, this longitudinal study seeks to understand the interwoven cognitive and social outcomes of participating in community-engaged art projects among college students. Informed by a theoretical framework in which CBAE situates learning in authentic social contexts, findings suggest that it may be decisively poised to yield short- and long-term educational benefits in which student learning deepens through the development of social connectedness. These findings expand the possibilities for collaboration as a pedagogical model for inclusive postsecondary education.